A Study on Thermal Behaviour of Thermoplastic Starch Plasticized by [Emim] Ac and by [Emim] Cl - Man, Zakaria (2017)
Thermoplastic starch (TPS) is a material that's been produced through a gelatinization process at elevated temperature in the presence of plasticizers. However, the hydrophilic properties of structural starch may decrease the thermal behaviour of TPS.